Case Report: Unraveling complex genomic alterations in a case of chronic lymphocytic leukemia using optical genome mapping - Youssefian, Leila; Sahoo, Trilochan; Wang, Jia-Chi (Frontiers in Oncology, 2025)
Chronic lymphocytic leukemia (CLL) is one of the most prevalent adult leukemias, derived from mature B-cells and exhibiting a highly heterogeneous disease course. Standard cytogenetic analysis of CLL includes FISH and karyotyping. However, conventional chromosome analysis of cancer specimens is often constrained by low chromosomal resolution, and FISH analysis is limited by the number of probes that can be applied. This study highlights the application of optical genome mapping (OGM), a high-resolution cytogenomic tool that visualizes ultra-long, sequence-labeled DNA molecules, to uncover the structural complexity of the cancer genome and assess the clinical relevance of chromothripsis in CLL. Comprehensive cytogenetic analysis was conducted on a 43-year-old male diagnosed with chronic lymphocytic leukemia. Karyotyping revealed a complex rearrangement: 46,XY,der(3)t(3;13)(p2?3;q14.3),der(4)t(?3;4)(p23;p16),add(11)(p13),del(13)(q14)[12]/46,sl,del(11)(q2?2.2q23.3)[6]. FISH analysis further identified the loss of ATM and a partial deletion of the D13S319 locus. OGM analysis performed on bone marrow revealed a complex genotype including chromothripsis of chromosome 13, and structural rearrangements involving chromosomes 3, 4, and 11. Additionally, multiple intrachromosomal translocations and interstitial microdeletions of chromosome 13 were identified. The resolution of these aberrations has been significantly enhanced with examples including: ogm[GRCh38] t(3;13)(p26.3;q33.1)(2,706,645~2,721,113;103,142,901~103,154,241][VAF0.45], ogm[GRCh38] t(4;13)(p15.31;q32.1)(20,869,721~20,907,265;96,617,837~96,630,317)[VAF0.42],. In conclusion, OGM revealed the intricate structural alterations of the cancer genome. The high resolution provided by OGM could facilitate the discovery of oncogenic mechanisms, novel fusion genes, prognostic markers, and potential therapeutic targets. OGM serves as a powerful tool for revisiting CLL disease classification by offering deeper insights into complex genomic rearrangements.